Interference of mouse polyomavirus with the c-myc gene and its product in mouse mammary adenocarcinomas - Holländerová, Dana; Raslová, Hana; Blangy, Daniel; Forstová, Jitka; Berebbi, Monique (International journal of oncology, 2003)
In two tumour sublines (T.wt/BL and T.wt/Bc), established from mammary adenocarcinomas caused by mouse polyoma (Py) infection of nu/nu mice, integration of polyomavirus DNA sequences into the c-myc gene locus was mapped. A complete Py genome was found to be integrated just upstream from the c-myc gene in T.wt/BL cell line, while only a part of the early Py region coding for the early proteins was inserted in the chromosomal DNA of T.wt/Bc cells. An interference of Py sequences with the regulation of c-myc gene expression gives further significance to a Py-derived tumour system that appears to be similar to some human mammary cancers in the modifications of c-myc expression. Both cell lines were found to produce truncated large T antigen and entire middle and small T antigens. In addition, production of VP1 protein was observed in the T.wt/BL cell line. The integration of polyomavirus sequences and/or expression of viral proteins caused an elevation of c-myc expression. The level of the c-myc expression was higher in both tumour cell lines in comparison with control normal murine mammary gland (NMuMG) lines, but substantially lower than in NMuMG cells infected with polyomavirus. Possible co-operation of Py proteins with c-Myc was examined. Through GST fusion protein pull-down experiments, we evidenced, that c-Myc forms a complex with the common part of the Py early antigens in the two tumour cell lines. Co-localisation of the c-myc and LT was observed in cells overexpressing c-Myc and LT.
Keywords: DNA, Neoplasm; experimentální nádory mléčných žláz; Mammary Neoplasms, Experimental; geny myc; Mammary Glands, Human; protoonkogenní proteiny c-myc; Virus Integration; glutathiontransferasa; Proto-Oncogene Proteins c-myc; Cell Transformation, Viral; DNA virů; adenokarcinom; Mice; mléčné žlázy lidské; Glutathione Transferase; Antigens, Polyomavirus Transforming; Polyomavirus; Genes, myc; virová transformace buněk; zvířata; Humans; DNA nádorová; DNA, Viral; myši; integrace viru; antigeny transformující polyomavirové; Adenocarcinoma; lidé; Animals